Propagation of the fast magnetosonic wave through the generalized Budden barrier - Kazakov, Ye.O.; Pavlenko, I.V.; Girka, I.O. (Національний науковий центр «Харківський фізико-технічний інститут» НАН України, 2010)
Propagation of the fast magnetosonic wave through the generalized Budden barrier, which is formed by the ion-ion hybrid resonance and the accompanying L-cutoff, is studied. Analytical expressions for the transmission, reflection and conversion coefficients are derived. It is shown that the nonzero reflection from the barrier arises in case of the wave incidence from the resonance side, and the conversion coefficient can reach the value 48.6% for the cutoff incidence case. The obtained results generalize the formulas of the Budden theory in case of the different fast wave wavelength at the opposite sides of the ion-ion hybrid resonance. Решена задача распространения быстрой магнитозвуковой волны через обобщенный барьер Баддена, который образован ион-ионным гибридным резонансом и связанной с ним L-отсечкой. Получены аналитические выражения для коэффициентов прохождения, отражения и конверсии. Показано, что имеет место ненулевое отражение от барьера в случае падения волны со стороны резонанса, а коэффициент конверсии может достигать величины 48.6% при падении волны со стороны отсечки. Полученные результаты обобщают формулы теории Баддена на случай различной длины волны по разные стороны от ион-ионного гибридного резонанса. Розв’язано задачу про поширення швидкої магнітозвукової хвилі крізь узагальнений бар’єр Баддена, який утворений іон-іонним гібридним резонансом та L-відсічкою, що пов’язана з ним. Здобуто аналітичні вирази для коефіцієнтів проходження, відбиття та конверсії. Показано, що має місце ненульове відбиття від бар’єру для випадку падіння хвилі зі сторони резонансу, а коефіцієнт конверсії може сягати величини 48.6% за умови падіння хвилі зі сторони відсічки. Здобуті результати узагальнюють формули теорії Баддена на випадок різної довжини хвилі по різні боки від іон-іонного гібридного резонансу.